Acts of the Constitutional Court as sources of law of the Republic of Kazakhstan - Kalmaganbetova, D.B.; Yessentemirova, А.M. (Bulletin of the Karaganda University “Law Series”, 2025)
Constitutional Court of the Republic of Kazakhstan has a significant role in overseeing observance of the country’s law and regulation in accordance with the Constitution. Its acts have an effect on law enforcement practice, influencing law and its creation. However, the question of exactly how the acts of the Constitutional Court have an effect on the country’s legal system and up to what extent they may be regarded as sources of law is still subject to research. The acts of the Constitutional Court play a significant role in strengthening and improving the legal system. The research task is to determine and understand the legal nature and role of acts of the Constitutional Court of the Republic of Kazakhstan as a source of law. The research employed system-atic and content analyses of normative legal acts, constitutional and judicial acts, and comparative legal method. The study determined that acts of the Constitutional Court possess strong legal force and have strong influence on processes of lawmaking and enforcement. Their acts are binding for everyone who are subjects of public authority and are legal guidelines for constitutional understanding. The acts proved to be definite sources of law and perform a role in ensuring constitutional order and human rights protection. The study stresses further development for applying these acts and for expanding a role of the Court in Kazakhstan’s le-gal system. The study results are operable during legislative development and during legal practice.